(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: The term maternal near miss refer to women who have escaped death either by chance or due to good health care after experiencing severe life threatening complications during pregnancy, labour and within six weeks after termination of pregnancy. Severe Acute Maternal Morbidity (SAMM) or Maternal Near Miss (MNM) is a complement of maternal mortality. The aim of this study is to state the need of patient’s health education, importance of emergency transportation as well as to evaluate the standard of effective quality & evidence based care in the facility to reduce maternal mortality and morbidity. Materials and methods : This observational study conducted for the period of January to December 2019 at Chattogram Maa-O-Shishu Hospital Medical College (CMOSHMC). Among 8976 total patients, MNM were 44 and total Maternal Death (MD) 13. Maternal Near miss clinical criteria – haemorrhage, hypertensive disorder of pregnancy, dystocia, sepsis & severe anaemia, organ dysfunction, based on management of ICU, blood transfusion, Maternal near miss are used to indicate quality of health care. Exclusion criteria- maternal death. Results: Total admitted patients in Obs & Gynae department in this study period were 8976. Obstetric patient 7422 & total deliveries 6027. MNM 44 in number & MD were 13. Main causes of MNM were hypertensive disorders (Severe preeclampsia, Eclampsia, HELLP syndrome)-23 (52.3%), obstetric haemorrhage (Placenta praevia, abruption placenta, rupture uterus, rupture ectopic pregnancy, incomplete abortion with shock, DIC)-14 (31.8%) Cardiopulmonary dysfunction (Cardiac arrest, cardiomyopathy, heart failure) – 7 (15.9%). Among the 44 near miss management, LSCS – 32 (73%) vaginal deliveries – 4 (9%), laparotomy – 5 (11%), peripartum hysterectomy – 3 (7%). Women with life threatening condition (MNM & MD) – 57. MNM ratio 6.8 per thousand live birth, MNM & MD ratio – 3.4:1 Conclusion : SAMM or MNM is a pro-indicator to improve quality of obstetric care. Monitoring the near miss morbidity in conjunction with mortality surveillance could help to identify effective preventable measure for potentially life threatening morbidity. Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 57-60